Design of Portable Intelligent Classification Cosmetic Cabinet Based on Image Processing - Meihua Zhang,; Linhan Wang,; Xinhao Wen,; Xiaojuan Xia,; Chunyan Zhang, (IJRDO -Journal of Computer Science Engineering, 2019)
A portable intelligent classification cosmetic cabinet based on image processing is proposed. Firstly, the structure of this intelligent classification cosmetic cabinet is designed in detail. Subsequently, the hardware and control principle are introduced. Finally, the control program is written in Python language, and the physical verification is carried out. Experimental result proves that the cosmetic cabinet can perform the expected functions, and the intelligent control of the cosmetic cabinet is realized by voice control.